Disentangling the facilitation effect of emoji in vocabulary recognition: experimental evidence from semantic matching tasks - Li, Yin; Zhong, Zilong (Frontiers in Psychology, 2025)
BackgroundIn the digital age, visual symbols such as emojis have become integral to everyday communication. Despite their ubiquity, the cognitive and educational functions of emojis remain underexplored, particularly in the context of second language (L2) learning.ObjectivesThis study aims to examine the potential of emojis as multimodal tools for enhancing vocabulary recognition in L2 learners. Specifically, it investigates whether emojis support more accurate and efficient semantic processing compared to traditional verbal translation methods.MethodsA 2 (text type: emoji–Chinese vs. English–Chinese) × 2 (task type: match vs. mismatch) within-subjects experimental design was employed. Thirty English-speaking learners of Chinese participated and completed a series of semantic matching tasks. Reaction times and accuracy were recorded to assess cognitive processing under each condition.ResultsParticipants demonstrated significantly faster response times and higher accuracy in the emoji–Chinese match condition compared to the English–Chinese condition, especially when semantic congruency was present. However, the facilitative effect of emojis was reduced in mismatch conditions, suggesting a context-dependent influence of visual symbols on learning outcomes.ConclusionThese findings highlight the potential of emojis as semiotic and cognitive resources in L2 vocabulary learning. The study underscores the importance of context-sensitive integration of visual media in instructional design, offering practical implications for enhancing language learning through multimodal approaches. The findings suggest that emoji can facilitate vocabulary recognition. However, the current results should be interpreted as evidence that emoji facilitate learners’ performance in semantic matching tasks, rather than evidence of long-term vocabulary acquisition. Future research should incorporate delayed post-tests and retention measures to examine whether emoji support durable learning outcomes.